2023
DOI: 10.1007/s13311-023-01434-9
|View full text |Cite
|
Sign up to set email alerts
|

Gys1 Antisense Therapy Prevents Disease-Driving Aggregates and Epileptiform Discharges in a Lafora Disease Mouse Model

Katherine J. Donohue,
Bethany Fitzsimmons,
Ronald C. Bruntz
et al.

Abstract: Patients with Lafora disease have a mutation in EPM2A or EPM2B, resulting in dysregulation of glycogen metabolism throughout the body and aberrant glycogen molecules that aggregate into Lafora bodies. Lafora bodies are particularly damaging in the brain, where the aggregation drives seizures with increasing severity and frequency, coupled with neurodegeneration. Previous work employed mouse genetic models to reduce glycogen synthesis by approximately 50%, and this strategy significantly reduced Lafora body for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…An imbalance between glycogen synthase and branching enzyme in favour of glycogen synthase appears to promote the formation of insoluble polyglucosan [8, 11]. Inhibition of glycogen synthase ameliorates polyglucosan storage disease in different animal experimental studies, including RBCK1 deficiency, branching enzyme deficiency and Lafora disease [12–14]. Inactivation by conditional knockout of the glycogenin gene in mice results in glycogen accumulation in muscle, indicating that glycogenin is involved in the regulation of glycogen content [15].…”
Section: Discussionmentioning
confidence: 99%
“…An imbalance between glycogen synthase and branching enzyme in favour of glycogen synthase appears to promote the formation of insoluble polyglucosan [8, 11]. Inhibition of glycogen synthase ameliorates polyglucosan storage disease in different animal experimental studies, including RBCK1 deficiency, branching enzyme deficiency and Lafora disease [12–14]. Inactivation by conditional knockout of the glycogenin gene in mice results in glycogen accumulation in muscle, indicating that glycogenin is involved in the regulation of glycogen content [15].…”
Section: Discussionmentioning
confidence: 99%
“…GYS1 serves as the key rate‐limiting enzyme in glycogen synthesis, 20 and its deficiency causes muscle glycogen storage disease type 0 and death at a pathological level 21,22 . Besides, previous studies have found that targeting the GYS1 could halt the progression of epilepsy and neuroinflammation 23–25 . Additionally, numerous studies have shown that GYS1 participates in tumor growth and progression through different mechanisms such as via the nuclear factor kappa‐B (NF‐κB) pathway, the AMP‐activated protein kinase (AMPK) pathway, and the hypoxic inducible factor‐1 alpha (HIF‐1α) pathway 26–28 .…”
Section: Introductionmentioning
confidence: 99%
“… 21 , 22 Besides, previous studies have found that targeting the GYS1 could halt the progression of epilepsy and neuroinflammation. 23 , 24 , 25 Additionally, numerous studies have shown that GYS1 participates in tumor growth and progression through different mechanisms such as via the nuclear factor kappa‐B (NF‐κB) pathway, the AMP‐activated protein kinase (AMPK) pathway, and the hypoxic inducible factor‐1 alpha (HIF‐1α) pathway. 26 , 27 , 28 The enzymatic function of GYS1 can be regulated through post‐translational modification and the influence of allosteric effectors.…”
Section: Introductionmentioning
confidence: 99%